Optimization of the host/vector system and culture conditions for production of penicillin acylase in Escherichia coli - Chou, C. P.; Kuo, B. Y.; Lin, W. J. (Journal of Bioscience and Bioengineering, 1999)
Culture performance for the production of penicillin acylase (PAC) in a bioreactor was investigated using HB101 or ATCC11105 as the host and pCLL2902, pCLL3201 or pTrcKnPAC2902 as the expression plasmid. We observed that the production of PAC by HB101 harboring pCLL3201 was, similar to ATCC11105, induced by phenyl acetic acid (PAA) and catabolically repressed by glucose, whereas the production of PAC by HB101 harboring pCLL2902 did not require PAA for induction and was not repressed by glucose. PAC activity of HB101 harboring pCLL2902 was significantly higher than that of HB101 harboring pCLL3201. There was no significant effect of host or carbon source on the production of PAC using pCLL2902, The production of PAC by HB101 harboring pTrcKnPAC2902, in which the pac gene expression was controlled by the trc promoter system, was about the same as that by HB101 harboring pCLL2902, when the culture was appropriately induced with isopropyl beta-D-thiogalactopyranoside (IPTG). Therefore, the use of both pCLL2902 and pTrcKnPAC2902 could be expected to be feasible for industrial applications. However, optimization of IPTG induction for HB101 harboring pTrcKnPAC2902 might be required, since formation of inclusion bodies tends to limit the production of PAC in some cases.